215k views
2 votes
Simplify [4a^(-6) b^2]^(-3) write your answer using only positive exponent

1 Answer

6 votes

For this case we must simplify the following expression:


(4a^( - 6) * b ^ 2)^( - 3)

By definition of power properties we have:
a ^ {-1} = \frac {1} {a ^ 1} = \frac {1} {a}

Then, rewriting the expression:


(\frac {4} {a ^ 6} * b ^ 2) ^ {- 3} =\\\frac {1} {(\frac {4} {a ^ 6} * b ^ 2)^3} =\\\frac {1} {(\frac {4b ^ 2} {a ^ 6})^3} =

By definition we have to:


(a ^ n) ^ m = a ^ {n * m}


\frac {1} {\frac {64b ^ 6} {a^(18)}}\\\frac {a^(18)} {64b ^ 6}

Answer:


\frac {a^(18)} {64b ^ 6}

User Toabi
by
6.4k points